A reexamination of the cognitive behavioral model of chronic fatigue syndrome - Sunnquist, Madison (J Clin Psychol, 2018)
OBJECTIVE: The cognitive behavioral model of chronic fatigue syndrome (CFS) suggests that cognitions and reduced activity level perpetuate the fatigue and impairment that individuals with CFS experience. The two empirical evaluations of this model resulted in conflicting findings. The current study examines the influence of case definition fulfillment on the applicability of this model to CFS. METHOD: A moderated mediation analysis was conducted on 990 individuals with CFS to reexamine the behavioral pathway of this model. Case definition fulfillment was entered as a moderator. RESULTS: Findings were generally inconsistent with the cognitive behavioral model of CFS. Case definition fulfillment significantly moderated the relation between activity level and physical impairment (β = –0.08, p = 0.03); individuals who met more stringent case definitions demonstrated a weaker relation between activity level and impairment. CONCLUSIONS: This model may not accurately represent the experience of individuals with CFS, particularly those who fulfill more stringent case definitions.